2020
DOI: 10.1097/prs.0000000000007278
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine Green Angiography Predicts Tissue Necrosis More Accurately Than Thermal Imaging and Near-Infrared Spectroscopy in a Rat Perforator Flap Model

Abstract: Background: Clinical examination alone is neither sensitive nor specific for predicting flap necrosis, so several technologies, including indocyanine green angiography, thermal imaging (using the FLIR ONE), and near-infrared spectroscopy, have been developed to supplement perfusion assessment. This study aims to compare the accuracy of these three methods for intraoperatively predicting clinical flap necrosis in a rat perforator flap model. The authors hypothesized that near-infrared spectroscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Therefore, small measurement inaccuracies must be assumed. For example, thermal imaging using FLIR ONE in a rat perforator model showed a sensitivity, specificity, and accuracy with a temperature difference of 80.8, 83.6, and 82 percent, respectively [ 45 ]. The assessment of burn wounds showed that the FLIR ONE was highly reliable, but with moderate validity [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, small measurement inaccuracies must be assumed. For example, thermal imaging using FLIR ONE in a rat perforator model showed a sensitivity, specificity, and accuracy with a temperature difference of 80.8, 83.6, and 82 percent, respectively [ 45 ]. The assessment of burn wounds showed that the FLIR ONE was highly reliable, but with moderate validity [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that ICGA is a valuable adjunct that can assess flap perfusion and identify HPAs. 4,6,9,12 Komorowska-Timek and Gurtner 24 reported that prophylactic excision of HPAs can minimize the incidence of mastectomy flap necrosis and impaired healing.…”
Section: Discussionmentioning
confidence: 99%
“…8 A recent study suggested that indocyanine green angiography (ICGA) appears to be the most accurate of these tools. 9 Since Still et al 10 first used ICGA to evaluate flap perfusion in 1999, this technique has been adapted for plastic and reconstructive surgeries. 11,12 The benefits of ICGA in assessing tissue perfusion to aid clinical decision-making have been demonstrated in mastectomy skin flaps, 13 free flaps, 12 and pedicle flaps.…”
mentioning
confidence: 99%
“…Most of the small animal model studies using ICG as a tool for assessing flap viability have taken place in rats. [15][16][17][18] Although the results have been promising in these select studies, it is important to appreciate the different mechanisms by which these studies quantify necrosis.…”
Section: Clinical Grading Assessment Of Flap Necrosismentioning
confidence: 99%